Barrier integrity and chronic inflammation mediated by HIF-1 impact on intestinal tumorigenesis. (10th October 2020) - Robrahn, Laura; Jiao, Long; Cramer, Thorsten
Abstract: Colorectal cancer ranks among the top three most frequent malignancies in the world. While overall incidence and mortality of colorectal cancer has substantially decreased in recent years, tumor subtypes with poor response rates to standard antiproliferative therapies remain particularly challenging. Hypoxia in the microenvironment of solid tumors is associated with malignant progression, e.g. local invasion, systemic spread and therapy resistance. A detailed molecular understanding of hypoxia's role for the pathobiology of colorectal cancer is a prerequisite to design and evaluate the consequences of interference with hypoxic signaling for the progression of this cancer type. Here, we summarize the current knowledge about the role of hypoxia-inducible factor 1, an essential molecular mediator of the hypoxic response, for colorectal cancer pathogenesis. Special attention is given to intestinal microbiota, gut barrier integrity and chronic inflammation as these are of pivotal importance for intestinal tumorigenesis and noticeably associated with hypoxic signaling. Highlights: Epithelial cells in the gut maintain their function in response to hypoxia. HIFs are important for intestinal physiology and disease. Stabilization of HIF-1 ameliorates intestinal inflammation in rodent models. Loss of HIF-1 in intestinal epithelial cells impairs intestinal tumorigenesis. Clinical trials addressing this in human patients are urgently anticipated.